(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the secret and methods that the healers assign in the Uzbek national medical system, the processes of the connected relationship between the teacher and the student, the examination of the doctors after the end of the study, the secrets passing from father to son are investigated. The author analyzed the social significance of the healer and his place in the preservation of tradition.